Upgrading, Downgrading, Linking, Innovating: Microfinance Development Strategies - A Systems Perspective - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1997)
In the transition process from financial repression to a prudentially deregulated financial system, an increasing number of developing countries are becoming concerned about access of the rural and urban masses to microfinance. Only viable institutions with sound practices, which mobilize their own resources and cover their costs from the margin, can respond to the increasing demand for microsavings, microcredit and microinsurance services on a sustainable basis. Three major approaches contribute to the development of a system of microfinance: reform of the policy environment; institutional transformation; and instrumental innovation. In this framework there is a wide variety of institutions that have to undergo major adjustments to play their role effectively as financial intermediaries for the microeconomy: commercial and development banks; formal local banks and semiformal financial institutions under private, cooperative, community or local government ownership; credit NGOs; and informal financial institutions. Contingent upon the policy environment, the institutional infrastructure, and the degree of market integration, there are four major strategies of institutional transformation: institutional adaptation, or downgrading, of formal financial institutions; institutional enhancement, or upgrading, of nonformal financial institutions; linking formal and nonformal financial institutions; and, in the absence of a sufficient number of adaptable formal and nonformal institutions, infrastructural innovation: establishing new microfinance institutions. In each case, sound financial practices appropriate to the institution and its market are essential. There is no single best approach that can be simply replicated without regard to the unique situation of a country or region.
Keywords: 330